A Situational Mapping Overview of Training Programmes for Community-Based Rehabilitation Workers in Southern Africa: Strategies for Strengthening Accessible Rural Rehabilitation Practice - Lieketseng Ned; Ritika Tiwari; Lucia Hess-April; Theresa Lorenzo; Usuf Chikte (Frontiers Media S.A., 2020)
In 2018, the United Nations global report showed that people with disabilities, who make up 15% of the worlds' population, have poorer health and rehabilitation access (SDG 3). Without improving the needed person-centered health and rehabilitation services at household level, SDG 3 cannot be achieved. This includes addressing human resource shortages through training multi-skilled community based rehabilitation workers (CRWs) to build rural workforce capacity and enhance the lives of people with disabilities, particularly in LMICs where the need is higher but resources are lower. However, to date, there is no documentation and analysis of existing training and its scope for this workforce in LMICs. A situational mapping overview was undertaken to review the current status of rural rehabilitation training programs offered in Southern Africa for CRWs. CRWs are rehabilitation personnel, based in the home/community, who are not professionals (without a bachelor qualification) but render non-institutional rehabilitation and inclusive development in communities, under the supervision of rehabilitation practitioners. Information on these programs was obtained using a two-step process. Firstly, a descriptive list of university courses for rehabilitation workers offered in the Southern African countries was collected via an internet and literature search. Secondly, detailed information about the disability and rural rehabilitation courses was collected from the respective institutions and their designated websites. There are six training courses targeted at CRWs or disability practitioners with a disability focus being offered at universities in Southern Africa, five of these in South Africa and one in Zimbabwe. Additionally, four training courses are offered as online/open resources by global organizations and are self-directed with no accreditation. While other key competencies feature, none of these programmes' learning outcomes make direct reference to the rural practice context and its complexities in relation to disability and poverty. The situational mapping overview shows limited training targeted at CRWs in Southern Africa, to effectively facilitate rural rehabilitation, poverty reduction and social inclusion. There is a need for an articulated community-orientated rural training to respond to the unmet needs. This may require a different set of competencies and assessment standards for trainees as well as additional competencies for their supervisors and mentors.